DRY SYSTEM LIVE FISH TRANSPORT SIMULATION TEST IN BEONG FISH (Hemibagrus nemurus) USING PLANTAIN STEM LIVER EXTRACT (Musa paradisiaca) WITH THE DIFFERENT DOSE - Wulandari, Vidya Setianti; Jailani, Abdul Qadir; Sari, Annisa Novita (Asian Journal of Aquatic Sciences, 2022)
Asian Redtail Catfish (Hemibagrus nemurus) is one of the freshwater fish commodities that lives on several rivers in Indonesia. Unavailability of Asian Redtail Catfish throughout Indonesia causing the provider area to become a target market for distributing Asian Redtail Catfish. This study aims to find out the effect of administering the optimal anesthetic dose of banana stem liver extract for anesthesia and the survival rate of Asian Redtail Catfish in dry system transportation testing. The research method used is the complete random design method (RAL) 3 treatments and 3 repetitions, where P1 (dose 1%), P2 (dose 2%), and P3 (dose 3%). The results showed that a dose of 1% banana stem liver extract gave the best results in the dry system transportation test process with a duration of 76 minutes 35 seconds, a conscious recovery duration of 7 minutes 1 second, and a survival rate. Survival rate Asian Redtail Catfish amounted to 94.43% of the total sample. This proves that the anesthesia of banana stem liver extract affects the survival rate of Asian Redtail Catfish with an optimum dose of 1% and further research is needed on dosing and the correlation between samples and variables.